2013
DOI: 10.1111/tesg.12065
|View full text |Cite
|
Sign up to set email alerts
|

The competitiveness of China's Leading Regions: Benchmarking Their Knowledge‐based Economies

Abstract: The Competitiveness of China's Leading Regions: Benchmarking their Knowledge-Based Economies AbstractChina's spectacular economic growth has been spatially uneven, with much development occurring in eastern coastal areas. In particular, three metropolitan 'super-regions' have become China's most competitive knowledge-based economies, consisting of the Pearl River Delta, the Yangtze River Delta, and the Bohai Gulf Region. This paper benchmarks the competitiveness of these regions, with a view to exploring which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 126 publications
0
18
0
Order By: Relevance
“…In verifying this argument, some recent empirical studies have clearly shown that firms tend to search for new cooperation actors or establish branches in similarly specialized clusters and/or metropolitan areas so as to obtain more unconscious knowledge spillover (Poon et al 2013;Boschma et al 2014;Gabe and Abel 2016). In addition, due to their importance for the availability of highly qualified labor (Ponds et al 2010;Huggins et al 2014), the presence of academic research institutes and universities is expected to influence the local actors' knowledge base and their innovation potential. Firms located in places with rich resource endowments are more likely to discover and utilize partners on different geographical scales (Wang and Lin 2013;Hewitt-dundas 2013).…”
Section: Regional Environmentmentioning
confidence: 94%
See 3 more Smart Citations
“…In verifying this argument, some recent empirical studies have clearly shown that firms tend to search for new cooperation actors or establish branches in similarly specialized clusters and/or metropolitan areas so as to obtain more unconscious knowledge spillover (Poon et al 2013;Boschma et al 2014;Gabe and Abel 2016). In addition, due to their importance for the availability of highly qualified labor (Ponds et al 2010;Huggins et al 2014), the presence of academic research institutes and universities is expected to influence the local actors' knowledge base and their innovation potential. Firms located in places with rich resource endowments are more likely to discover and utilize partners on different geographical scales (Wang and Lin 2013;Hewitt-dundas 2013).…”
Section: Regional Environmentmentioning
confidence: 94%
“…On the one hand, in the context of the more stable Northern culture, it is easier to establish local or provincial linkages through guanxi networks, such as the recommendations by friends and relatives (Liefner and Zeng 2008). On the other hand, the effect of administrative borders and protectionism in Northern parts is much more powerful, therefore firms switch their innovation focus towards co-localized partners to catch R&D support from the government (Huggins et al 2014;Jiang et al 2017).…”
Section: Determinants Of the Spatial Character Of China's Innovation mentioning
confidence: 99%
See 2 more Smart Citations
“…Regions are the primary spatial units of organization that compete to attract investment; thus, the attention has turned to competitiveness at a more regional level (Huggins et al 2016). Competitiveness is a multidimensional and complex category that characterizes a market economy.…”
Section: Literature Reviewmentioning
confidence: 99%